2011
DOI: 10.1042/bj20110033
|View full text |Cite
|
Sign up to set email alerts
|

S6K inhibition renders cardiac protection against myocardial infarction through PDK1 phosphorylation of Akt

Abstract: In the present study, we observed a rapid and robust activation of the ribosomal protein S6K (S6 kinase) provoked by MI (myocardial infarction) in mice. As activation of S6K promotes cell growth, we hypothesized that increased S6K activity contributes to pathological cardiac remodelling after MI and that suppression of S6K activation may prevent aberrant cardiac remodelling and improve cardiac function. In mice, administration of rapamycin effectively suppressed S6K activation in the heart and significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 46 publications
2
53
0
Order By: Relevance
“…This may explain the preferential effect of PF-4708671 on Akt S473 and not Akt T308-as revealed by immunoblot analysis of Akt phosphorylation sites in FAO cells and insulin target tissues of HF-fed obese mice. In line with these results, PF-4708671 has been also shown to be cardioprotective against myocardial infarction in mice by increasing Akt phosphorylation [37]. Thus, increased Akt activity likely plays a major role in the beneficial metabolic outcomes of S6K1 inhibition by PF-4708671.…”
Section: Discussionsupporting
confidence: 66%
“…This may explain the preferential effect of PF-4708671 on Akt S473 and not Akt T308-as revealed by immunoblot analysis of Akt phosphorylation sites in FAO cells and insulin target tissues of HF-fed obese mice. In line with these results, PF-4708671 has been also shown to be cardioprotective against myocardial infarction in mice by increasing Akt phosphorylation [37]. Thus, increased Akt activity likely plays a major role in the beneficial metabolic outcomes of S6K1 inhibition by PF-4708671.…”
Section: Discussionsupporting
confidence: 66%
“…Rapamycin treatment of mice was as previously described (20). Potassium bisperoxo(1,10-phenanthroline)oxovanadate [bpV(phen)] was purchased from Santa Cruz (sc-221378A) and was administered to mice intraperitoneally at 2 weeks after birth for 7 days at a dose of 6.6 mg/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that long-term treatment of mice with rapamycin abolished Akt S473 in the heart while enhancing Akt T308 phosphorylation, which is cardiac protective (20). This study suggests that mTOR is responsible for Akt S473 phosphorylation.…”
mentioning
confidence: 96%
“…The previously described mouse strains used in this study included Pten conditional mice (Suzuki et al, 2001), Mesp1-Cre and Mef2c-AHF-Cre mice (Klaus and Birchmeier, 2009;Saga et al, 1999;Verzi et al, 2005), β-cateninfloxed mice (Huelsken et al, 2001) and Akt1 and Pdk1 conditional mice (Di et al, 2012;Feng et al, 2010;Zhao et al, 2014). All mouse lines were maintained in a B6 genetic background.…”
Section: Micementioning
confidence: 99%